Alignment of clinical competencies in nursing education: an umbrella review - Rincón, Daniel (2025)
Objective: To identify, in the scientific literature on nursing education, the predominant curricular elements in the processes of incorporating the clinical competence-based approach. Competency-based education in the health field faces tensions derived from the transition from a traditional educational model to a competency-based one. Method: An umbrella review of scientific literature was conducted through a search in ten sources, including databases and scientific publishers: Science Direct, Web of Science, PubMed, EBSCO, Scopus, Embase, Dialnet, SciELO, Redalyc, and Springer. The Joanna Briggs Institute review protocol was adopted, which includes selection criteria, search strategy, study selection, methodological quality assessment, data collection, and synthesis. Inclusion criteria were: nursing students, clinical competencies, and literature reviews; exclusion criteria: reviews from other health disciplines, graduate-level nursing studies, and professional competencies. Results: Nine reviews published between 2014 and 2024 were selected and analyzed using the constructive alignment approach, focusing on three key elements: the concept of clinical competencies and their typologies; the use of simulation as a teaching strategy; and the methodologies and tools used for their assessment. Conclusions: The findings reveal divergent interpretations of the concept of clinical competencies, divided views on the educational value of simulation, and fragmented evaluation approaches. This highlights the need for specific training of educators in competency-based education to ensure implementation aligned with the proposed learning outcomes.